Effect of Sowing Methods and NPK Levels on Growth and Yield of Rainfed Maize (Zea mays L.). (18th May 2015) - Gul, Shamim; Khan, M. H.; Khanday, B. A.; Nabi, Sabeena
Abstract : To investigate the response of rainfed maize to sowing methods and NPK levels, an experiment was undertaken during kharif of 2011 and 2012 at Dryland (Kerawa) Agriculture Research Station, Sher-e-Kashmir University of Agricultural Sciences and Technology of Kashmir, Budgam. The experiment was laid out in a randomized block design with combination of 2 sowing methods (flat sowing, 75 cm apart rows, and ridge sowing, 75 cm apart ridges) and 3 fertility levels (60 : 40 : 20, 75 : 50 : 30, and 90 : 60 : 40 N : P2 O5 : K2 O kg ha −1 ) with three replications. Various growth characters, namely, plant height, leaf area index, dry matter accumulation, number of days to different phenological stages, and yield, and yield contributing characters namely, cob length, number of grains cob −1, cob diameter (cm), and 100-seed weight (g), were significantly higher with S2 over S1 during both the years of experimentation. Fertilizer levels F3 (90 : 60 : 40) and F2 (75 : 50 : 30) at par with one another produced significant increase in growth and yield characters, namely, plant height, leaf area index, dry matter production at different growth stages, cob length, number of cobs plant −1, number of grains cob −1, and 100-seed weight over F1 (60 : 40 : 20). Significantly higher grain yield was recorded with fertilizer level F3 (90 : 60 : 40) being at par with F2 (75 : 50 : 30) and showed significant increase over F1 (60 : 40 : 20) with superiority of 5.4 and 5.7 per cent during 2011 and 2012, respectively. The findings of the study concluded that ridge method of sowing of maize with NPK levels of 75 : 50 : 30 kg ha −1 showed better performance of crop in terms of growth, yield, and yield attributes.